Oxidation in foods and beverages and antioxidant applications. Volume 1, - McClements, David Julian; Decker, Eric, 1960-; Elias, Ryan J. (Woodhead Publishing in food science, technology, and nutrition ;, 2010)
Oxidative rancidity is a major cause of food quality deterioration, leading to the formation of undesirable off-flavours as well as unhealthful compounds. Antioxidants are widely employed to inhibit oxidation, and with current consumer concerns about synthetic additives and natural antioxidants are of much interest. The two volumes of Oxidation in foods and beverages and antioxidant applications review food quality deterioration due to oxidation and methods for its control. The first volume focuses on oxidation mechanisms and antioxidant activity. Initial chapters in part one describe oxidation processes in foods, including the role of metals, heme proteins and lipoxygenase. The impact of oxidation on food flavour and the health aspects of oxidized fats are also covered. Final chapters in part one review the measurement of the extent of lipid oxidation and methods for food shelf-life determination. Part two discusses the ways in which antioxidants inhibit food oxidation, factors affecting antioxidant efficacy, methods to measure antioxidant activity and novel antioxidants. With its distinguished international team of editors and contributors, the two volumes of Oxidation in foods and beverages and antioxidant applications is standard references for R & D and QA professionals in the food industry, as well as academic researchers interested in food quality. Describes oxidation processes in foods, including the role of metals, heme proteins and lipoxygenaseReviews the impact of oxidation on food flavour and the health aspects of oxidized fatsDiscusses the ways in which antioxidants inhibit food oxidation, factors affecting antioxidant efficacy and methods to measure antioxidant activity.